2020
DOI: 10.1001/jamaophthalmol.2020.0412
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parental Myopia With Higher Risk of Myopia Among Multiethnic Children Before School Age

Abstract: IMPORTANCE Parental myopia is an important risk factor for preschool myopia in Asian children. Further investigation of the association between parental myopia and early-onset myopia risk in other racial/ethnic groups, such as African American and Hispanic white children, could improve understanding of the etiology and treatment of this condition.OBJECTIVE To investigate the association of parental myopia with refractive error and ocular biometry in multiethnic children aged 6 to 72 months. DESIGN, SETTING, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
8
37
0
Order By: Relevance
“…Consistent with other longitudinal studies, we also found a higher risk of myopia in children with two myopic parents compared with those in one- and no-myopic-parent families [ 35 37 ]. However, we did not find a statistically significant difference between children having only one myopic parent and children not having a myopic parent in the risk of myopia onset.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other longitudinal studies, we also found a higher risk of myopia in children with two myopic parents compared with those in one- and no-myopic-parent families [ 35 37 ]. However, we did not find a statistically significant difference between children having only one myopic parent and children not having a myopic parent in the risk of myopia onset.…”
Section: Discussionsupporting
confidence: 92%
“…171 A purely genetic explanation for rare, monogenic (syndromic) forms of myopia is clear, but the impact of parental myopia is also seen for school myopia. Studies covering a range of different ethnic groups have shown that having one or two parents with myopia increases the risk of myopia in children, 26,[172][173][174][175][176][177][178] although the relative risk is naturally lower in populations with a high baseline prevalence of myopia.…”
Section: Ethnicity Ethnicity or Race Has Often Been Proposedmentioning
confidence: 99%
“…71 However, parental myopia was associated with a greater risk of early-onset myopia in a recent study. 75 Cognitive functions and education. Education seems to be important in triggering the onset of myopia, but less important in determining the degree to which myopia progresses.…”
Section: Personal Characteristicsmentioning
confidence: 99%